Center For Zakat Management (Czm) And Its Role In Poverty Eradication In Bangladesh - Mohammad Osmani, Noor; Al Masud, Abdullah (Universiti Sains Islam Malaysia, 2024)
Centre for Zakat Management (CZM) introduced a new mechanism of payment, utilization, mobilization and effective distribution of Zakat in an organized and planned manner to achieve significant success in poverty eradication in Bangladesh. CZM adopted prime initiatives for institutionalizing Zakat management system aiming to promote prosperity and raise standard of living of the poor communities in Bangladesh. CZM provides zakat to the needy people in order to improve their living standard through income generating activities. The main objective of this paper is to examine the activities of CZM and its role in upgrading the living standard of needy people. Primary data are collected from the project area especially from Manikganj District of Bangladesh that received zakat under Jibeeka project of CZM. The data are also collected from the head office of CZM, Dhaka, Bangladesh. It is expected that the similar steps could be adopted in the different parts of the Muslim world to eradicate poverty from the society.